Revives My Soul Again: Martin Luther King, Jr. and Classic Wisdom of the Discernment of Spirits - Immel, Eric (Lumen et Vita, 2022)
The work of Dr. Martin Luther King Jr. remains deeply influential in justice discourse. In this paper, the author employs classic wisdom of the discernment of spirits to explore whether King’s words can be determined as influenced by the Holy Spirit. While the impact of King’s writing and speeches are not in doubt, the question of divine influence is important to consider as issues of racial and economic justice persist today. Focusing specifically on three of King’s works (“The Letter from Birmingham Jail,” “I Have a Dream,” and “I Have Been to the Mountaintop”), the author argues that these works align with markers of the Holy Spirit at work, and as such, King’s words remain vital to the pursuit of justice today on the social and spiritual levels.